At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To determine the relationship between [tex]\( x \)[/tex] and [tex]\( y \)[/tex] in the given table, we need to analyze how [tex]\( y \)[/tex] changes as [tex]\( x \)[/tex] changes.
[tex]\[ \begin{array}{|c|c|c|c|c|c|} \hline x & 3 & 4 & 6 & 8 & 12 \\ \hline y & 16 & 12 & 8 & 6 & 4 \\ \hline \end{array} \][/tex]
One way to understand this is by finding the product of each pair [tex]\( (x, y) \)[/tex]. If [tex]\( y \)[/tex] varies inversely as [tex]\( x \)[/tex], then the product [tex]\( x \cdot y \)[/tex] should be constant.
Let's calculate the product of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] for each pair:
1. For [tex]\( x = 3 \)[/tex] and [tex]\( y = 16 \)[/tex]:
[tex]\[ 3 \cdot 16 = 48 \][/tex]
2. For [tex]\( x = 4 \)[/tex] and [tex]\( y = 12 \)[/tex]:
[tex]\[ 4 \cdot 12 = 48 \][/tex]
3. For [tex]\( x = 6 \)[/tex] and [tex]\( y = 8 \)[/tex]:
[tex]\[ 6 \cdot 8 = 48 \][/tex]
4. For [tex]\( x = 8 \)[/tex] and [tex]\( y = 6 \)[/tex]:
[tex]\[ 8 \cdot 6 = 48 \][/tex]
5. For [tex]\( x = 12 \)[/tex] and [tex]\( y = 4 \)[/tex]:
[tex]\[ 12 \cdot 4 = 48 \][/tex]
Since the product [tex]\( x \cdot y \)[/tex] is constant (48) for all pairs, we can conclude that [tex]\( y \)[/tex] varies inversely as [tex]\( x \)[/tex].
Therefore, the correct statement of variation is:
C. [tex]\( y \)[/tex] varies inversely as [tex]\( x \)[/tex]
[tex]\[ \begin{array}{|c|c|c|c|c|c|} \hline x & 3 & 4 & 6 & 8 & 12 \\ \hline y & 16 & 12 & 8 & 6 & 4 \\ \hline \end{array} \][/tex]
One way to understand this is by finding the product of each pair [tex]\( (x, y) \)[/tex]. If [tex]\( y \)[/tex] varies inversely as [tex]\( x \)[/tex], then the product [tex]\( x \cdot y \)[/tex] should be constant.
Let's calculate the product of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] for each pair:
1. For [tex]\( x = 3 \)[/tex] and [tex]\( y = 16 \)[/tex]:
[tex]\[ 3 \cdot 16 = 48 \][/tex]
2. For [tex]\( x = 4 \)[/tex] and [tex]\( y = 12 \)[/tex]:
[tex]\[ 4 \cdot 12 = 48 \][/tex]
3. For [tex]\( x = 6 \)[/tex] and [tex]\( y = 8 \)[/tex]:
[tex]\[ 6 \cdot 8 = 48 \][/tex]
4. For [tex]\( x = 8 \)[/tex] and [tex]\( y = 6 \)[/tex]:
[tex]\[ 8 \cdot 6 = 48 \][/tex]
5. For [tex]\( x = 12 \)[/tex] and [tex]\( y = 4 \)[/tex]:
[tex]\[ 12 \cdot 4 = 48 \][/tex]
Since the product [tex]\( x \cdot y \)[/tex] is constant (48) for all pairs, we can conclude that [tex]\( y \)[/tex] varies inversely as [tex]\( x \)[/tex].
Therefore, the correct statement of variation is:
C. [tex]\( y \)[/tex] varies inversely as [tex]\( x \)[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.